2022
DOI: 10.1177/17534666221075499
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute exacerbation of chronic obstructive pulmonary disease under a tiered medical system in China

Abstract: Background: The Chinese government has promoted the ‘tiered medical services’ policy in which diseases are classified by severity, mode of onset and difficulty of treatment since 2015 to optimize medical resources. We evaluated the diagnosis and treatment of acute exacerbation (AE) of chronic obstructive pulmonary disease (AECOPD) under the tiered system. Methods: We conducted a cross-sectional study. COPD characteristics and treatments were compared among hospitals in different tiers. Associations were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Both VCV and PCV were able to effectively manage patients with AECOPD and respiratory failure, as demonstrated by improvements in the respiratory rate, tidal volume, arterial blood gas values (including pH, PaO 2 , and PaCO 2 ), and oxygenation indices (PaO 2 /FiO 2 ratio) during their ICU stay. This observation was consistent with a previous studies, thus suggesting that both ventilation modes can be used successfully to treat patients with AECOPD suffering from the respiratory failure[ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Both VCV and PCV were able to effectively manage patients with AECOPD and respiratory failure, as demonstrated by improvements in the respiratory rate, tidal volume, arterial blood gas values (including pH, PaO 2 , and PaCO 2 ), and oxygenation indices (PaO 2 /FiO 2 ratio) during their ICU stay. This observation was consistent with a previous studies, thus suggesting that both ventilation modes can be used successfully to treat patients with AECOPD suffering from the respiratory failure[ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Corticosteroids account for a large proportion of AECOPD treatments. In a study from China, in a medication analysis of 432 eligible AECOPD patients, the proportion of glucocorticoids applied increased with hospital grade (18.6% vs. 45.6% vs. 69.2%; p < 0.001) ( Liu et al, 2022 ). A cross-sectional study by the Veterans Health Administration in 2020 found that 23.9% of 26,536 patients with COPD without a history of severe or frequent exacerbations and without airflow disorders were treated with inhaled corticosteroids ( Griffith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that the majority of tertiary hospitals were located in urban versus rural areas (64.7% versus 35.3%), and others have shown that patients prefer to access a local hospital when they have an acute exacerbation. 28 In the REAL study, there were more patients with severe disease in secondary versus tertiary hospitals, and together with our data on treatment patterns, this indicates that many patients may not have received adequate treatment. Vogelmeier et al 12 reported that just over half the patients with one moderate baseline exacerbation and over one-third (36.9%) of patients with one severe baseline or multiple baseline exacerbations were not prescribed inhaled maintenance treatment at diagnosis, underscoring the importance of timely and appropriate prescription of pharmacological treatment in patients with stable COPD.…”
Section: Discussionmentioning
confidence: 65%
“…Finally, Chinese patients may prefer to combine TCM with pharmacological treatment, as shown in a recent survey on treatment preference among patients with COPD in China, 44 and this could be due to TCM being more affordable, especially to patients living in rural areas. 28 …”
Section: Discussionmentioning
confidence: 99%